Development of a U.S. fine wool selection index - Kott, Tamra L. (Kansas State University, 2022)
Genetic evaluation in the United States (U.S.) sheep industry has previously lacked emphasis on fine wool quality traits. The Western range index (WRI) was the only index provided through National Sheep Improvement Program (NSIP) to include grease fleece weight (GFW) and fiber diameter (FD). As the market shifts and the military continue to support U.S. wool, greater emphasis on the selection of fine wool quality and production is needed to meet the needs of shifting market conditions. The objectives of this thesis were to estimate economic drivers of fine wool production and provide U.S. producers with an effective fine wool selection index to evaluate the genetic performance of fine wool production. Breeding objectives were developed through evaluation of survey responses obtained from production, marketing, and processing sectors of the sheep industry. Respondents across all sectors indicated that FD, GFW, staple length (SL), staple strength (SS), character, body weight (BW), and fleece yield (YLD) should be included in a selection index. Through adjustments due to database constraints and measurement limitations, the final traits included in the breeding objective were FD, GFW, SL, fiber diameter coefficient of variation (FDCV), and curvature (CURV). Economic values were determined through communications with fine wool industry leaders and available market information (6.08 or 5.75 for GFW, -0.227 or -0.124 for FD, 0 for SL, -0.039 for FDCV, and 0.0042 for CURV) and led to the development of four potential indices. Due to severe economic nonlinearity in SL, the economic values were applied to restricted matrix calculations to produce a restricted index weight for SL. The economic values and the restricted index weight of SL were then used to evaluate each index for sensitivity to economic weights. Overall, efficiency loss was less than 1% across the four indices, indicating they were all robust to changes in economic values. The final index proposed for the NSIP database was 6.08 GFW – 0.227 FD – 0.099 SL – 0.039 FDCV + 0.0042 CURV as it was the fastest, most aggressive approach to selection for increased GFW and decreased FD. Selection utilizing this index is expected to emphasize increased GFW and decreased FD, whereas decreased FDCV and increased CURV were given minimal importance. Due to the index restriction, SL is expected to remain the same. Overall, the proposed U.S. fine wool index may be utilized to increase fine wool production and quality.
Keywords: Selection index; Sheep; Wool; Survey